التوبة في الإسلام - Che' Sarehan Suhana Che' Othman (Universiti Sains Islam Malaysia, 2009)
This research is been help especially to discuss about the concept of repentance in Islamic religion. The main point of this study to investigate about the important repentance in human life, as we h o w that there never escape from a sin. By the way, this study also give us awareness that without repentance some one cannot get the blessing from the Allah S.W.T . h the chapter one this study discuss about the meaning of repentance from language and from istilah and then the opinion of ulamak about the repentance. In this chapter , the writer also investigate about "dalil-dalil" to show the some one must be repentance in their life. After that, writer also to discuss about hokum and condition of repentance . In the second chapter , the study discuss about accept the repentance of munafiq , murtad , and also repentance from zindiq . In the third chapter , the writer presented about , the track of repentence in dropped of hudud. In this research the writer is use library rnetod at KUIM library , Tun Sri Lanang library and Islamic library.